2016
DOI: 10.1021/acs.orglett.6b01753
|View full text |Cite
|
Sign up to set email alerts
|

Radical and Nitrenoid Reactivity of 3-Halo-3-phenyldiazirines

Abstract: 3-Halo-3-phenyl-3H-diazirines (halogen = Br or Cl) undergo a dissociative single-electron transfer from alkyllithiums (RLi) in THF-based solvent mixtures. The resulting 3-phenyldiazirinyl radical, observed by EPR spectroscopy, is eventually transformed to benzonitrile. In Et2O, 2 equiv of RLi add to both nitrogens of halodiazirine N═N bond, affording N,N'-dialkylbenzamidines. The nitrenoid reactivity of some N-alkyl-1H-diazirine intermediates is manifested by their insertion into the α-C-H bond of THF or Et2O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A few years later, Richards introduced a trifluoromethyl group in aromatic series to further stabilize the carbene . Interestingly, the reactivity of halodiazirines was widely studied because they are easily prepared from nitriles using Graham’s method . In recent years, new practical applications for diazirines were disclosed; they were used as carbon radical traps in amination processes, as carbene sources for the formation of sulfur ylides, as electrophilic nitrogen sources in the synthesis of pyrazoles, and as reagents in the Pd-catalyzed cross-coupling reactions with aryl halides, or even in oxidative cross-coupling reactions with aryl boronic acid .…”
Section: Introductionmentioning
confidence: 99%
“…A few years later, Richards introduced a trifluoromethyl group in aromatic series to further stabilize the carbene . Interestingly, the reactivity of halodiazirines was widely studied because they are easily prepared from nitriles using Graham’s method . In recent years, new practical applications for diazirines were disclosed; they were used as carbon radical traps in amination processes, as carbene sources for the formation of sulfur ylides, as electrophilic nitrogen sources in the synthesis of pyrazoles, and as reagents in the Pd-catalyzed cross-coupling reactions with aryl halides, or even in oxidative cross-coupling reactions with aryl boronic acid .…”
Section: Introductionmentioning
confidence: 99%
“…43 Another theory could be that polymerization is initiated via a diazirinyl radical or other reactive intermediates within the transition state. 44 It is also speculated that the mechanism may be similar to that of common dialkyl diazene radical polymerization initiators. 45 The crosslinked insoluble nature of cured glue makes discerning reaction products difficult, let alone reactive intermediates, so further studies are needed to ascertain the nature of the reaction.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have indicated that the expected reaction products of triplet carbenes are not observed for TPDs, and others have indicated that the triplets are observed but in smaller quantities than the singlet carbene . Another theory could be that polymerization is initiated via a diazirinyl radical or other reactive intermediates within the transition state . It is also speculated that the mechanism may be similar to that of common dialkyl diazene radical polymerization initiators .…”
Section: Discussionmentioning
confidence: 99%